KELAYAKAN TEKNO-EKONOMI SISTEM IRIGASI CURAH, TETES DAN KENDI PADA BUDIDAYA TANAMAN MELON (Cucumis Melo, L.) - Hasbi . (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT The objective of this study was to determine the most suitable irrigation system consisted of sprinkler, drip and picther for melon crof cultivation in dry land having the same soil type, as well as to evaluate its financial feasibility at business scale.the study was conducted in two stages. The first stage was planting of melon cropof Sky Rocket variety using each of the irrigation systems. The second stage was to carry out analysis on the technical and financial feasibilities. The technical feasibility consisted of water supply analysis, evapotranspiration analysis, efficiency of land that could be utilized, whereas the financial feasibility consisted of NPV, Net B/C, BEP and sensitivy analysis. The result showed that the three irrigation systemswere technically feasible to be applied for melon crop cultivation. This was shomn by normal weekly growth of melon crop and good average production yield of the melon crop. The three irrigation systems (sprinkler, drip and pitcher) were financially feasible as they had NPV and Net B/C values that were greater than the reference values. Results of sensitivity analysis to 10% of cost increase and 10% of selling price decrease showed that the three irrigation systems above were still feasible to be applied for melon crop cultivation as their NPV and B/C values were greater than the refrence values.. Keyword : melon, technical and financial feasibility, sensitivity analysis.